The Doris Day and Rock Hudson comedy collection [videorecording (DVD)] - Gordon, Michael, 1909-1993; Mann, Delbert, 1920-2007; Jewison, Norman, 1926-; Hudson, Rock, 1925-1985; Day, Doris, 1922-2019-; Randall, Tony; Ritter, Thelma (Universal Studios Home Entertainment, 2007)
Pillow talk: Two single professionals find themselves sharing a party line - and a whole lot more - when they get their lines crossed. Lover come back: Business gets mixed with pleasure when two advertising executives go after the same account. Send me no flowers: A hypochrondriac gets the wrong diagnosis and decides to arrange for a 'future' husband for his very confused wife.